KEBIJAKAN ELEKTRONIK KARTU TANDA PENDUDUK (E-KTP) DI KECAMATAN PLUMPANG KABUPATEN TUBAN - Noviana,; Musrifah, Sri (Istiqra: jurnal hasil penelitian, 2023)
The current development of information and communication technology presents several general principles that can guide every organization or institution in making strategic policies. Like preparing priority programs, in this case, is the government. So, one of the government's priority programs is government services to the community, namely the service of making Electronic Identity Cards (E-KTP). From this explanation, this research aims to find out how the E-KTP policy is implemented and the obstacles faced by the Government at the Plumpang District level, Tuban Regency. This research is qualitative, data collection starts from observation, documentation, and in-depth interviews. After the data was collected, it was analyzed descriptively qualitatively, giving rise to the conclusion that the E-KTP policy in Plumpang District, Tuban Regency started with socialization activities, data collection, and handing over summons to residents and then recording. Meanwhile, there are six obstacles faced in implementing the E-KTP policy in the Plumpang sub-district, Tuban district. firstly, there are still residents who have not been registered, second, the resources of employees implementing e-KTP are not ready, thirdly, socialization from the government regarding e-KTP is still unclear, fourthly there is a lack of equipment facilities, fifthly there is a lack of communication and coordination carried out by the government, and sixthly there is a lack of discipline E-KTP operator employee. From this conclusion, authorized officials at the Plumpang District level can discipline E-KTP operator employees, because the basic service of the Plumpang District government to the community is the service in making E-KTP